Multi-proxy paleohydrological and paleoecological reconstruction of a subaquatic cave in western Cuba - Matthew C. Peros; Shawn Collins; Joao Gabriel Martínez-López; Lázaro W. Viñola López; Miguel Angel Pereira Sosa; Laurence Forget Brisson; François Hardy; Michel Lamothe; Peter J. van Hengstum; Bil Phillips; Kenneth Broad; Jill Heinerth; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Heterogeneous Perceptions of Social-Ecological Change Among Small-Scale Fishermen in the Central Gulf of California: Implications for Adaptive Response - Timothy H. Frawley; Larry B. Crowder; Kenneth Broad (Frontiers in Marine Science, 2019)

Avoiding a crisis of motivation for ocean management under global environmental change - Peter J. Mumby; James N. Sanchirico; Kenneth Broad; Michael W. Beck; Peter Tyedmers; Megan Morikawa; Thomas A. Okey; Larry B. Crowder; Elizabeth A. Fulton; Denny Kelso; Joanie A. Kleypas; Stephan B. Munch; et al. (Global Change Biology, 2017)
Climate change and ocean acidification are altering marine ecosystems and, from a human perspective, creating both winners and losers. Human responses to these changes are complex, but may result in reduced government investments in regulation, resource management, monitoring and enforcement. Moreover, a lack of peoples’ experience of climate change may drive some towards attributing the symptoms of climate change to more familiar causes such as management failure. Taken together, we anticipate that management could become weaker and less effective as climate change continues. Using diverse case studies, including the decline of coral reefs, coastal defences from flooding, shifting fish stocks and the emergence of new shipping opportunities in the Arctic, we argue that human interests are better served by increased investments in resource management. But greater government investment in management does not simply mean more of “business‐as‐usual.” Management needs to become more flexible, better at anticipating and responding to surprise, and able to facilitate change where it is desirable. A range of technological, economic, communication and governance solutions exists to help transform management. While not all have been tested, judicious application of the most appropriate solutions should help humanity adapt to novel circumstances and seek opportunity where possible.

Sea Snake Harvest in the Gulf of Thailand - NGUYEN VAN CAO; NGUYEN THIEN TAO; AMELIA MOORE; ALFRED MONTOYA; ARNE REDSTED RASMUSSEN; KENNETH BROAD; HAROLD K. VORIS; ZOLTAN TAKACS (Conservation Biology, 2014)
Conservation of sea snakes is virtually nonexistent in Asia, and its role in human–snake interactions in terms of catch, trade, and snakebites as an occupational hazard is mostly unexplored. We collected data on sea snake landings from the Gulf of Thailand, a hotspot for sea snake harvest by squid fishers operating out of the ports of Song Doc and Khanh Hoi, Ca Mau Province, Vietnam. The data were collected during documentation of the steps of the trading process and through interviewers with participants in the trade. Squid vessels return to ports once per lunar synodic cycle and fishers sell snakes to merchants who sort, package, and ship the snakes to various destinations in Vietnam and China for human consumption and as a source of traditional remedies. Annually, 82 t, roughly equal to 225,500 individuals, of live sea snakes are brought to ports. To our knowledge, this rate of harvest constitutes one of the largest venomous snake and marine reptile harvest activities in the world today. Lapemis curtus and Hydrophis cyanocinctus constituted about 85% of the snake biomass, and Acalyptophis peronii, Aipysurus eydouxii, Hydrophis atriceps, H. belcheri, H. lamberti , and H. ornatus made up the remainder. Our results establish a quantitative baseline for characteristics of catch, trade, and uses of sea snakes. Other key observations include the timing of the trade to the lunar cycle, a decline of sea snakes harvested over the study period (approximately 30% decline in mass over 4 years), and the treatment of sea snake bites with rhinoceros horn. Emerging markets in Southeast Asia drive the harvest of venomous sea snakes in the Gulf of Thailand and sea snake bites present a potentially lethal occupational hazard. We call for implementation of monitoring programs to further address the conservation implications of this large‐scale marine reptile exploitation. Cosecha de Serpientes Marinas en el Golfo de Tailandia

The art of the science: climate forecasts for wildfire management in the southeastern United States - Carla Roncoli; Norman Breuer; David Zierden; Clyde Fraisse; Kenneth Broad; Gerrit Hoogenboom (Climatic Change, 2012)

Coral Reef Habitats as Surrogates of Species, Ecological Functions, and Ecosystem Services - PETER J. MUMBY; KENNETH BROAD; DANIEL R. BRUMBAUGH; CRAIG, P. DAHLGREN; ALASTAIR R. HARBORNE; ALAN HASTINGS; KATHERINE E. HOLMES; CARRIE V. KAPPEL; FIORENZA MICHELI; JAMES N. SANCHIRICO (Conservation Biology, 2008)
Habitat maps are often the core spatially consistent data set on which marine reserve networks are designed, but their efficacy as surrogates for species richness and applicability to other conservation measures is poorly understood. Combining an analysis of field survey data, literature review, and expert assessment by a multidisciplinary working group, we examined the degree to which Caribbean coastal habitats provide useful planning information on 4 conservation measures: species richness, the ecological functions of fish species, ecosystem processes, and ecosystem services. Approximately one‐quarter to one‐third of benthic invertebrate species and fish species (disaggregated by life phase; hereafter fish species) occurred in a single habitat, and Montastraea ‐dominated forereefs consistently had the highest richness of all species, processes, and services. All 11 habitats were needed to represent all 277 fish species in the seascape, although reducing the conservation target to 95% of species approximately halved the number of habitats required to ensure representation. Species accumulation indices (SAIs) were used to compare the efficacy of surrogates and revealed that fish species were a more appropriate surrogate of benthic species (SAI = 71%) than benthic species were for fishes (SAI = 42%). Species of reef fishes were also distributed more widely across the seascape than invertebrates and therefore their use as a surrogate simultaneously included mangroves, sea grass, and coral reef habitats. Functional classes of fishes served as effective surrogates of fish and benthic species which, given their ease to survey, makes them a particularly useful measure for conservation planning. Ecosystem processes and services exhibited great redundancy among habitats and were ineffective as surrogates of species. Therefore, processes and services in this case were generally unsuitable for a complementarity‐based approach to reserve design. In contrast, the representation of species or functional classes ensured inclusion of all processes and services in the reserve network.

Institutional Evolution in Lake Okeechobee Management in Florida: Characteristics, Impacts, and Limitations - Neeraj Vedwan; Sajjad Ahmad; Fernando Miralles-Wilhelm; Kenneth Broad; David Letson; Guillermo Podesta (Water Resources Management, 2008)

Climate, stream flow prediction and water management in northeast Brazil: societal trends and forecast value - Kenneth Broad; Alexander Pfaff; Renzo Taddei; A. Sankarasubramanian; Upmanu Lall; Franciso de Assis de Souza Filho (Climatic Change, 2007)

Environmental ‘loopholes’ and fish population dynamics: comparative pattern recognition with focus on El Niño effects in the Pacific - Andrew Bakun; Kenneth Broad (Fisheries Oceanography, 2003)
A process of comparative pattern recognition is undertaken for the purpose of garnering insights into the mechanisms underlying some currently puzzling conundrums in fishery resource ecology. These include (a) out‐of‐phase oscillations between anchovies and sardines, (b) the remarkable fish productivity of the Peru–Humboldt marine ecosystem, (c) sardine population increases in the eastern Pacific during El Niños, (d) basin‐wide synchronies in large‐amplitude abundance variations, (e) characteristic spawning of large tuna species in poorly productive areas, (f) contrary trends in Pacific tropical tuna abundance during the 1970s and early 1980s. It is found that each of the items appears to become less enigmatic when the conceptual focus shifts from conventional trophodynamics to the idea that ‘loopholes’ in the fields of biological controls (i.e. of predators of early life stages), produced by poor ocean productivity or by disruptive environmental perturbations, may in fact lead to remarkable reproductive success. Implications include the following: (1) El Niño, rather than being an unmitigated disaster for Peruvian fisheries, may in the long run be a prime reason for the remarkable fishery productivity of the Peru–Humboldt large marine ecosystem. (2) Globally‐teleconnected climatic trends or shifts might produce globally‐coherent population expansions even when local environmental expressions may be quite different. (3) It may be unreasonable to expect any management methodologies to be able to keep the fish populations of highly climatically‐perturbed systems such as the Peruvian LME always at stable high levels; an alternative approach, for example, might be to take optimal advantage of the transient opportunities afforded by the high fish productivity of such inherently erratic systems.

Effective and Equitable Dissemination of Seasonal-to-Interannual Climate Forecasts: Policy Implications from the Peruvian Fishery during El Niño 1997–98 - Kenneth Broad; Alexander S. P. Pfaff; Michael H. Glantz (Climatic Change, 2002)

Stanley A. Changnon (ed.), El Niño 1997–98: The Climate Event of the Century - Kenneth Broad (Climatic Change, 2002)

The IRI–IPRC Pacific Climate‐Fisheries Workshop - Andrew Bakun; Kenneth Broad (Fisheries Oceanography, 2002)